Efeitos da terapia fotodinâmica antimicrobiana na descontaminação de alvéolos com lesão periapical imediatamente pós-exodontia - Vasconcelos, Ximena Trévia Prado de (2014)
Advances in dentistry, with special attention to the use of immediate implants, have aroused interest in reviewing the aspects related to the subject, such as success and survival rate, treatment protocols for contaminated sites and microbiota found. The present work contains 2 chapters. In the first chapter a systematic review of scientific articles in the English language was performed using the terms immediate implant placement, fresh socket, dental implants, dated between 2003 and 2013, in the databases Bireme, Medline and The Cochrane Library. A total of 131 titles were found, of which 23 abstracts were selected and 6 articles fulfilled the inclusion criteria, which were: prospective randomized clinical trials, with a minimum sampling of 10 immediate implants on contaminated alveoli and a minimum of 12 months of follow-up. It was verified that the success rate of the immediate implants in contaminated sites is around 90 to 100% and the clinical protocol includes the debridement of the alveolus after exodontia and systemic antibiotic therapy pre and postoperative. The second chapter corresponds to a controlled clinical study, in which the effect of antimicrobial photodynamic therapy (TFA) mediated by 0.005% (AM) methylene blue associated with 90-second irradiation with low power laser, 40 mW, of 660 Nm, in the decontamination of periapical lesion dental alveoli after exodontia. We selected 16 patients with indication of extraction of 2 uniradicular elements. After the exodontia, blood samples were collected by inserting sterile absorbent paper cones into each well, which were stored in tubes containing Reduced Transport Fluid. One of the wells was filled with the AM solution and, after 5 minutes, irradiated (P + L +). The other well was filled with AM solution for 5 minutes without irradiation (P + L-). After the intervention, new blood collection was performed. Samples were diluted and seeded in triplicate in Petri dishes containing Blood Agar and enriched BHI. The plates with Blood Agar were incubated in aerobiose for 2 days and those with Brain Heart Infusion (BHI) in anaerobic for 7 days at 37 ° C. The colony-forming units were counted and the data were converted into base 10 logarithms, which were submitted to paired Student's t-test (α = 0.05). The results obtained showed a reduction in the CFU / mL count for aerobic (2.5 log) and anaerobic (1.5 log) bacteria in the P + L + groups, but with no statistically significant difference in relation to the P + L- ( P> 0.05). TFA showed a tendency to reduce contamination in alveoli with periapical lesion, just as AM showed to have an antimicrobial potential in these lesions, independently of laser irradiation. More studies are required with different concentrations of AM and different potencies and times of irradiation of the light source, in order to obtain greater effectiveness for a decontamination protocol alternative to the need for antibiotic therapy reported in the literature.